Pressure Induced Suppression to the Valence Change Transition in EuPdAs - Baoxuan Li; Jianzhong Liu; Yufeng Li; Xiyu Zhu; Hai-Hu Wen (Advances in Condensed Matter Physics)
By applying a hydrostatic pressure, we have successfully suppressed the valence change transition in EuPdAs. The studied compound EuPdAs crystallizes in a P63/mmc space group. Through resistivity and magnetic susceptibility measurements, we find that EuPdAs shows a phase transition at 180 K and another transition below 10 K at ambient pressure, as was reported before. The overall transport and magnetic behavior is to some extent similar to that of the parent phase of iron based superconductors. With application of a hydrostatic pressure, the transition at 180 K is sensitively suppressed with a pressure as low as 0.48 GPa. However, superconductivity has not been induced with pressure up to 1.90 GPa.